2007
DOI: 10.1152/ajpregu.00351.2006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mechanisms of the lateral parabrachial nucleus in renal and hormonal responses to isotonic blood volume expansion

Abstract: This study investigated the involvement of serotonergic mechanisms of the lateral parabrachial nucleus (LPBN) in the control of sodium (Na ϩ ) excretion, potassium (K ϩ ) excretion, and urinary volume in unanesthetized rats subjected to acute isotonic blood volume expansion (0.15 M NaCl, 2 ml/100 g of body wt over 1 min) or control rats. Plasma oxytocin (OT), vasopressin (VP), and atrial natriuretic peptide (ANP) levels were also determined in the same protocol. Male Wistar rats with stainless steel cannulas i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 58 publications
2
18
1
Order By: Relevance
“…In contrast to results from previous works [28,44], groups of cell-dehydrated rats that received methysergide or vehicle also had similar plasma concentrations of OT and AVP. The differences between the previous and present findings could relate in part to different procedures to challenge body-fluid balance.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to results from previous works [28,44], groups of cell-dehydrated rats that received methysergide or vehicle also had similar plasma concentrations of OT and AVP. The differences between the previous and present findings could relate in part to different procedures to challenge body-fluid balance.…”
Section: Discussioncontrasting
confidence: 99%
“…The differences between the previous and present findings could relate in part to different procedures to challenge body-fluid balance. Examples of different procedures are isotonic blood expansion or extracellular dehydration in previous works [28,44] in contrast to cell dehydration in the present work. Another possible difference is timing of blood collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the 5HT agonist (5HT2A/2C, 2,5-dimethoxy-4-iodoamphetamine hydrobromide), injected into the LPBN, increased the renal and endocrine response after EVE and inhibited sodium intake induced by different experimental models [15][20].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, it has been demonstrated that serotonergic terminals of the LPBN originating from DRN serotonergic somas also participate in the regulation of renal and hormonal responses induced by an isotonic increase in the ECF 30. Animals with electrolytic lesions of the DRN or with serotonin depletion induced by the central administration of p -chlorophenylalanine display attenuated ANP release, both under resting conditions and after extracellular volume expansion 31.…”
Section: Main Neural Pathways Involved In the Regulation Of Ecf Volummentioning
confidence: 99%